Opium's long shadow : from Asian revolt to global drug control - Rimner, Steffen, 1983- (Harvard University Press, 2018)
The League of Nations Advisory Committee on the Traffic in Opium and Other Dangerous Drugs, created in 1920, reversed almost eight decades of political turmoil over opium trafficking, which was by far the largest state-backed drug trade in the age of empire. Opponents of opium had long struggled to rein in the profitable drug. Opium's Long Shadow shows how diverse local protests crossed imperial, national, and colonial boundaries to gain traction globally and harness public opinion as a moral deterrent in international politics after World War I. Steffen Rimner traces the far-flung itineraries and trenchant arguments of reformers--significantly, feminists and journalists--who viewed opium addiction as a root cause of poverty, famine, "white slavery," and moral degradation. These activists targeted the international reputation of drug-trading governments, first and foremost Great Britain, British India, and Japan, becoming pioneers of the global political tactic we today call naming and shaming. But rather than taking sole responsibility for their own behavior, states in turn appropriated anti-drug criticism to shame fellow sovereigns around the globe. Consequently, participation in drug control became a prerequisite for membership in the twentieth-century international community.--